Pediatric Pleomorphic Xanthoastrocytoma with Neoplastic Meningitis: A Case Report with Cytopathological Evidence with Literature Review - Karanth, K. S. Vishwakumar; Bhattacharjee, Suchanda; Reddy, Ramanadha; Uppin, Megha (Indian Journal of Neurosurgery, 2023)
Pleomorphic xanthoastrocytoma (PXA) was regarded as grade II tumor and considered to be associated with favorable outcome. The World Health Organization Central Nervous System 5 (WHO CNS5) has classified PXA under circumscribed astrocytic gliomas and graded 2 or 3 depending on histology. Cerebrospinal fluid (CSF) and leptomeningeal spread are observed rarely in these tumors. The present case report describes a PXA, grade 3 tumor in a young male with neoplastic meningitis. This 17-year-old male child presented with history of seizure, signs of raised intracranial pressure, and meningeal irritation. Well-defined, T2 heterogeneously hyperintense lesion (5.5*4.8 cm) was seen in right frontal lobe with mild heterogenous contrast enhancement and adjacent pachy-meningeal enhancement. Right frontal craniotomy and near total excision were done. Postoperative hydrocephalus was treated with CSF diversion. Histopathology showed epithelioid and rhabdoid morphology with significant cellular pleomorphism and atypical mitosis consistent with the PXA, grade 3. The CSF cytology showed numerous tumor cells with marked nuclear and cytoplasmic pleomorphism. PXA is a rare malignancy of children and young adults, commonly seen in the temporal lobes. BRAF point mutations of V600E type are most common in PXA, grade 2. Meningeal dissemination is uncommon in PXA and its presence marks poor outcome. PXA, grade 2 tumors could be followed with serial imaging following gross total resection. PXA, grade 3 tumors are managed with maximal-safe resection, radiotherapy, and/ or chemotherapy. PXA, grade 3 with CSF spread tends to have rapid decline in the clinical course and it is advisable to get routine baseline and follow-up craniospinal screening and needs aggressive management.
Keywords: neoplastic meningitis; other astrocytic tumors; pleomorphic xanthoastrocytoma